2011
DOI: 10.1063/1.3592264
|View full text |Cite
|
Sign up to set email alerts
|

Anneal treatment to reduce the creation rate of light-induced metastable defects in device-quality hydrogenated amorphous silicon

Abstract: Nucleation rate reduction through stress relief of thermally annealed hydrogenated amorphous silicon films J. Appl. Phys. 113, 173509 (2013); 10.1063/1.4803686Light-induced changes in the gap states above midgap of hydrogenated amorphous silicon

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 19 publications
1
6
0
1
Order By: Relevance
“…For example, the agglomeration of two divacancies of which one is not fully hydrogen-passivated, as can occur in process I, leads to a fully hydrogen-passivated tetravacancy: V 2 H 4 + V 2 H 6 → V 4 H 10 . Such an improved hydrogen passivation degree could be the reason for the reduced LID that was recently observed for a-Si:H annealed at 350-400 °C prior to light soaking [86].…”
Section: Structural Model Describing the Evolution Of Open Volume mentioning
confidence: 99%
“…For example, the agglomeration of two divacancies of which one is not fully hydrogen-passivated, as can occur in process I, leads to a fully hydrogen-passivated tetravacancy: V 2 H 4 + V 2 H 6 → V 4 H 10 . Such an improved hydrogen passivation degree could be the reason for the reduced LID that was recently observed for a-Si:H annealed at 350-400 °C prior to light soaking [86].…”
Section: Structural Model Describing the Evolution Of Open Volume mentioning
confidence: 99%
“…First we have to notice that hydrogen within the structure diffuses to the top layer during annealing where it is trapped on the defects (dangling bonds) or effuses. Previous works have proposed that the N layer of the PIN is more damaged during light-soaking generating more dangling bonds, which are in turn, high absorption sites for the diffusing hydrogen during annealing [12]. From the evolution of Raman before and after light-soaking, we show that this long range motion of hydrogen causes a rearrangement and crystallization on the film followed by an increase of the interfaces.…”
Section: Methodsmentioning
confidence: 87%
“…Nuclear magnetic resonance (NMR) studies [ 5 ] on a ‐Si:H samples have indicated that the motion of H atoms, which are produced by the light‐induced breaking of SiH bonds, plays an important part in recovering the photovoltaic stability of the affected a ‐Si:H samples upon annealing at 350–400 °C. [ 6 ] Thus, an understanding of the motion of H atoms in a ‐Si in the presence of inhomogeneities is of crucial importance to address the photovoltaic stability of a ‐Si:H upon light irradiation.…”
Section: Introductionmentioning
confidence: 99%